A new freshwater species of Neorhynchoplax Sakai, 1938 (Crustacea: Decapoda: Hymenosomatidae) from Patna, Bihar, India - Ng, Peter K. L.; Nesemann, Hasko F.; Sharma, Gopal (Zootaxa, 2011)
A new species of hymenosomatid freshwater crab, Neorhynchoplax Sakai, 1938, is described from Patna, Bihar, northern India. The species resembles the Indian N. woodmasoni (Alcock, 1895) and N. alcocki Kemp, 1917, but differs in the form of the carapace, armature on the cheliped merus, number of spines on the dactylus of the ambulatory legs, and structure of the male abdomen.